2010
DOI: 10.3109/01443615.2010.505672
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of cysts/abscesses of Bartholin's gland: Review of empirical antibiotic therapy against microbial culture

Abstract: Bartholin's glands are prone to obstruction at their opening into the vestibule, forming cysts which could be infected to become gland abscess. In our unit, treatment of Bartholin's abscess is usually surgical. In addition to surgical treatment, antimicrobial agents are often administered before microbial culture results are known. In this study, we aimed to determine the most common pathogens in Bartholin's glands abscess in our local population so that empiric antimicrobial therapy, if required, could be cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 10 publications
8
23
1
1
Order By: Relevance
“…Careful attention should be made to strategies that may reduce the risk of recurrence by ensuring that operators are well trained, the cavity is completely evacuated, and antibiotics are tailored to microbiology sensitivities; these approaches are known to reduce rates of recurrence and prevent morbidity including postoperative sepsis. 19,20 Whatever treatment is offered, all women with a symptomatic cyst or abscess of the Bartholin's gland should be counselled regarding the high risk of future recurrence. The recurrence rates reported within our review are consistent with the recurrence rates reported in the published literature, which range from 2.7 to 17.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Careful attention should be made to strategies that may reduce the risk of recurrence by ensuring that operators are well trained, the cavity is completely evacuated, and antibiotics are tailored to microbiology sensitivities; these approaches are known to reduce rates of recurrence and prevent morbidity including postoperative sepsis. 19,20 Whatever treatment is offered, all women with a symptomatic cyst or abscess of the Bartholin's gland should be counselled regarding the high risk of future recurrence. The recurrence rates reported within our review are consistent with the recurrence rates reported in the published literature, which range from 2.7 to 17.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Bartholin's gland cysts and abscesses are the commonest gynaecological cystic disease of the vulva occurring in gynaecological practice all over the world as cystic growth of the labia majora [1].…”
Section: Introductionmentioning
confidence: 99%
“…Bartholin's glands are a well-known and studied part of the another alternative less invasive approach is marsupialisation, which is used for the treatment of cysts but not preferable in cases where the abscess is noted [3].…”
Section: Discussionmentioning
confidence: 99%